Role of ʻUlamāʻ in Islamization of the Constitution of Pakistan during 1947-1949 (Al-Qamar, 2020)
Early history of Pakistan shows that the westernized leadership of newly established Pakistan in 1947 to 1949 tried their best to make Pakistan a secular state. It was the result of steady pressure by ʻUlamāʻ that played a key role in a fundamental constitutional development based on Islamic Ideology. They rendered noteworthy services for this goal. This paper endeavors to highlight the significant services of different ʻUlamāʻ for Islamization of the constitution of Pakistan. It concludes that ʻUlamāʻ battled day and night to make Pakistan an Islamic state. They strongly rejected the modernists’ notion that Islam was a system for crude and tribal society of seventh century Arabia. The struggle by ʻUlamāʻ eventually met with success providing the constitution of Pakistan an Islamic perspective.
Keywords: Pakistan; Constitution; ʻUlamāʻ; Islamization